Nature and mode of addition of phosphate precursor in the synthesis of aluminum phosphate and its influence on methanol dehydration to dimethyl ether - Kumar, V. Siva; Padmasri, A. H.; Satyanarayana, C. V. V.; Reddy, I. Ajit Kumar; Raju, B. David; Rao, K. S. Rama (Catalysis Communications, 2006)
Four aluminum phosphate catalysts with Al/P = 1 were prepared by precipitation of mixture of aluminum nitrate and phosphate precursor (either phosphoric acid or diammonium hydrogen phosphate) with NH3 and precipitation of aluminum nitrate with NH3 followed by impregnation of phosphate precursor (either phosphoric acid or diammonium hydrogen phosphate). The catalysts were characterized, using different physico-chemical methods viz., BET-S.A., XRD, FT-IR, and NH3-TPD. Al-27 and P-31 MAS NMR spectroscopy was used to characterize selected catalysts in order to find out the presence of Al and P environments. The catalytic conversion of methanol to dimethyl ether was conducted over these catalysts in a temperature range of 448-548 K at atmospheric pressure. AIPO(4) prepared by precipitating the mixture of aluminum nitrate and (NH4)(2)HPO4 with aq. NH3 generated more number of moderate acid sites and showed higher methanol dehydration activity with 100% selectivity to DME at 548 K. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Al-27 and P-31 MAS NMR; aluminum phosphate; dehydration; dimethyl ether; Methanol; NH3-TPD